Maqasid Syariah as the Foundation of Religious Moderation in a Multicultural Society: A Conceptual Analysis of Strengthening Social Benefits - Ramadhanty, Krisnanda Alifia; Choiri, Moh. Miftachul; Ni'mah, Lailatun; Rifai, Mohammad Rohman; Zahiduzzaka, Muhammad Faza; Ngadimah, Mambaul (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study to analyze the relationship between Maqasid Syariah and religious moderation in strengthening social welfare within multicultural societies. The research employed a qualitative approach through library research. The primary data sources consisted of the Qur'an, Hadith, classical and contemporary Islamic scholarship on Maqasid Shariah, as well as scientific publications discussing religious moderation and multiculturalism. Data were analyzed using thematic analysis by identifying, categorizing, and synthesizing key themes related to the objectives of Islamic law and the principles of religious moderation. The findings indicate that Maqasid Shariah, through the principles of preserving religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), lineage (hifz al-nasl), and property (hifz al-mal), provides a normative foundation for promoting tolerance, social justice, peaceful coexistence, and resistance to radicalism. The novelty of this study lies in its conceptual synthesis that systematically links the objectives of Maqasid Shariah with indicators of religious moderation and social welfare in multicultural contexts. The study contributes theoretically by enriching the discourse on religious moderation through a maqasid-syariah framework that bridges Islamic normative values with contemporary social realities. Therefore, Maqasid Shariah serves not only as a legal objective but also as a conceptual foundation for strengthening social welfare and harmonious coexistence in multicultural societies.